2013
DOI: 10.4187/respcare.02278
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital-Wide Use of a Tapered-Cuff Endotracheal Tube on the Incidence of Ventilator-Associated Pneumonia

Abstract: BACKGROUND: Aspiration of colonized oropharyngeal secretions is a major factor in the pathogenesis of ventilator-associated pneumonia (VAP). A tapered-cuff endotracheal tube (ETT) has been demonstrated to reduce aspiration around the cuff. Whether these properties are efficacious in reducing VAP is not known. METHODS: This 2-period, investigator-initiated observational study was designed to assess the efficacy of a tapered-cuff ETT to reduce the VAP rate. All intubated, mechanically ventilated patients over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
5
17
0
2
Order By: Relevance
“…The rate of VAP obtained in our study is 2.06 cases per 1000 ventilator days similar to a study conducted by Bowton DL et al 23 However, a study by Panwar et al 24 reported the VAP rate as 26 per 1000 ventilator days. …”
Section: Discussion:-supporting
confidence: 76%
“…The rate of VAP obtained in our study is 2.06 cases per 1000 ventilator days similar to a study conducted by Bowton DL et al 23 However, a study by Panwar et al 24 reported the VAP rate as 26 per 1000 ventilator days. …”
Section: Discussion:-supporting
confidence: 76%
“…These hypotheses were confirmed in a bench (10) and a pilot study (16). Whether this improved sealing translates in to VAP reduction remains unanswered, since studies have yielded conflicting results: (6,11,28,29).…”
Section: Discussionmentioning
confidence: 56%
“…Dye was injected above the cuff, and fluid leakage was assessed by bronchoscopy periodically for up to 2 h. While dye in the trachea was seen in 20% of subjects with the cylindrical cuff, none was seen in those with the tapered cuff. Bowton et al 128 reported the impact of a hospital-wide conversion from a standard cylindrical PVC-cuffed ETT to a tapered PVC-cuffed ETT. They reported no difference in VAP rate during either 6-month study period: mean monthly rate of 3.3 Ϯ 1.8/1,000 ventilator days versus 2.8 ϩ 2.0/1,000 ventilator days for the cylindrical and tapered cuff groups, respectively, although the authors noted that their historic VAP rate was 5.8/1,000 ventilator days.…”
Section: Endotracheal Tube Design To Reduce Ventilator-associated Pnementioning
confidence: 99%
“…They reported no difference in VAP rate during either 6-month study period: mean monthly rate of 3.3 Ϯ 1.8/1,000 ventilator days versus 2.8 ϩ 2.0/1,000 ventilator days for the cylindrical and tapered cuff groups, respectively, although the authors noted that their historic VAP rate was 5.8/1,000 ventilator days. 128 A novel cuff design recently reported by Hwang et al 129 involves attaching a second PVC cuff to a standard ETT separated by 5 mm (Fig. 11).…”
Section: Endotracheal Tube Design To Reduce Ventilator-associated Pnementioning
confidence: 99%